Aristolochic acid induces renal fibrosis by arresting proximal tubular cells in G2/M phase mediated by HIF‐1α. Issue 9 (24th July 2020) - Zhao, Hao; Jiang, Na; Han, Yachun; Yang, Ming; Gao, Peng; Xiong, Xiaofen; Xiong, Shan; Zeng, Lingfeng; Xiao, Ying; Wei, Ling; Li, Li; Li, Chenrui; et al.
Abstract: Renal tubulointerstitial fibrosis (TIF) is a common pathological feature of aristolochic acid (AA) nephropathy (AAN). G2/M arrest of proximal tubular cells (PTCs) is implicated in renal fibrosis of AAN, but the upstream regulatory molecule remains unknown. Hypoxia inducible factor‐1α (HIF‐1α) promotes renal fibrosis in kidney disease, but the role of HIF‐1α in AAN is unclear. Evidence shows that HIF‐1α and p21, a known inducer of cellular G2/M arrest, are closely related to each other. To investigate the role of HIF‐1α in renal fibrosis of AAN and its effects on p21 expression and PTCs G2/M arrest, mice with HIF‐1α gene knockout PTCs (PT‐HIF‐1α‐KO) were generated, and AAN was induced by AA. In vitro tests were conducted on the human PTCs line HK‐2 and primary mouse PTCs. HIF‐1α and p21 expression, fibrogenesis, and G2/M arrest of PTCs were determined. Results showed that HIF‐1α was upregulated in the kidneys of wild‐type (WT) AAN mice, accompanied by p21 upregulation, PTCs G2/M arrest and renal fibrosis, and these alterations were reversed in PT‐HIF‐1α‐KO AAN mice. Similar results were observed in HK‐2 cells and were further confirmed in primary PTCs from PT‐HIF‐1α‐KO and WT mice. Inhibiting p21 in HK‐2 cells and primary PTCs did not change the expression of HIF‐1α, but G2/M arrest and fibrogenesis were reduced. These data indicate that HIF‐1α plays a key role in renal fibrosis in AAN by inducing PTCs G2/M arrest modulated through p21. HIF‐1α may serve as a potential therapeutic target for AAN.